The Development of Problem-Based Learning LKPD to Improve Students’ Critical Thinking Ability in The Fifth Grade of Primary School (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
The objective of the study is to create a PBL-based LKPD product that is feasible to improve critical thinking skills and determine the effectiveness of PBL-based LKPD products in enhancing critical thinking skills using T-test value analysis from pretest and posttest data. The research was conducted in the fifth grade of SD Negeri 4 Candimas consisting of 33 students. The type of study used Research and Development (R&D) carried out referring to the Borg & Gall design model. The results of this study were following the results of the development feasibility test to get results > 86, so it can be categorized as very good. In the t-test value, the value of Sig. (2-tailed) of 0.000 <0.05, so as the basis for decision making in the independent sample t-test, it can be concluded that H0 was rejected and H1 was accepted. Thus, it is concluded that the implementation of PBL-based LKPD is effectively used to improve students' critical thinking skills.